Measurement invariance of the Behavioural Regulation in Sport Questionnaire when completed by young athletes across five European countries - Viladrich, C.; Appleton, P.; Quested, E.; Duda, J.; Alcaraz, S.; Heuzé, J.; Fabra, P.; Samdal, O.; Ommundsen, Y.; Hill, A.; Zourbanos, N.; Ntoumanis, Nikos (Taylor & Francis Inc., 2013)
The purpose of this study was (1) to examine the factorial validity of the Behavioural Regulation Sport in Questionnaire (BRSQ) when completed by young soccer players in the Promoting Adolescent Physical Activity (PAPA) project (9-15 years old) in 5 European countries (France: n = 1248, Greece: n = 1507, Norway: n = 1397, Spain: n = 2245, and England: n = 1372) and (2) test the measurement invariance of its latent factors across these 5 countries. First, we tested the exploratory structural equation model (ESEM) factor analyses, allowing cross-loadings between factors, against the traditional independent clusters confirmatory factor analysis model (ICM-CFA), with all cross-loadings constrained to zero. The ESEM showed very Good Fit Indices, whereas the ICM-CFA was not tenable across countries. Second, the ESEM was used as the baseline model for the tests of factor loading (metric) invariance and factor loading plus thresholds (scalar) invariance. The five factors obtained from the analysis were scalar invariant and interpretable across the five countries (languages) as intrinsic motivation, identified, introjected and external regulations, and amotivation, in line with the tenets of self-determination theory). This study contributes to methodological advances in sport psychology, as it is the first time an adaptation of the BRSQ for young participants has been factor analysed comparing the more flexible ESEM to the usual ICM-CFA. Our data clearly favour using the more flexible weak dimensionality model (ESEM) and suggest a fresh interpretation of previous results may be required.